#### Answer

$-1(x+5)(x-1)$

#### Work Step by Step

Factor out $-1$ to obtain:
$=-1(x^2+4x-5)$
The leading coefficient of the trinomial is $1$.
This means that the trinomial can be factored by looking for the factors of the constant term $(-5)$ whose sum is equal to the coefficient of the middle term. $(4)$.
Note that:
$-5 = 5(-1)$ and $5+(-1) = 4$
Thus, the factors we are looking for are $5$ and $-1$.
This means that the factors of the trinomial are $x+5$ and $x-1$.
Therefore, the completely factored form of the given polynomial is:
$=-1(x+5)(x-1)$